2019
DOI: 10.3389/fonc.2019.01038
|View full text |Cite
|
Sign up to set email alerts
|

m6A RNA Methylation Regulators Contribute to Malignant Progression and Have Clinical Prognostic Impact in Gastric Cancer

Abstract: N6-methyladenosine (m6A) is the most common form of mRNA modification, and is dynamically regulated by the m6A RNA methylation regulators. However, little is known about m6A in gastric cancer. The aim of this work is to investigate the effects of m6A RNA methylation regulators in gastric cancer. Here, we found that most of the 13 main m6A RNA methylation regulators are higher expressed in 375 patients with gastric cancer. We identified two subgroups of gastric cancer (cluster1 and 2) by applying consensus clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 40 publications
(39 reference statements)
4
82
1
Order By: Relevance
“…Comparable results were also reported in other studies. It is reported that m6A regulator genes were extremely important in several cancer-related pathways, such as p53 signaling pathway [29,53], cell cycle [29,30,54], Ras [30], in ammatory response [29,53], and PPAR signaling pathway [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable results were also reported in other studies. It is reported that m6A regulator genes were extremely important in several cancer-related pathways, such as p53 signaling pathway [29,53], cell cycle [29,30,54], Ras [30], in ammatory response [29,53], and PPAR signaling pathway [53].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, m6A regulator genes are not only promising to become the potential molecular markers for cancer diagnosis and prognosis, but also quali ed to serve as the targets for the design of targeted anticancer drugs, which has been demonstrated in several literatures [26][27][28]. Several studies have investigated the role of m6A regulator genes in the survival of cancers, such as glioma [29], gastric cancer [30], and head and neck squamous cell carcinoma [31]. However, they did not include the newly discovered m6A regulator genes, seldom constructed a m6A-based nomogram, and never investigated the association with immunity Therefore, in this study, we systematically evaluated the expression of twenty m6A regulator genes in 535 lung ADC and 59 normal samples, from which we screened out seventeen differentially expressed genes for further study.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA-sequencing transcriptome data and clinicopathological information of 160 ESCA patients and 11 normal samples were obtained from The Cancer Genome Atlas (https://cancergenome.nih.gov/) database. Data procession was performed as the previous studies [15,16]. GSE13898 dataset was downloaded from the GEO database (https://www.ncbi.nlm.nih.gov/geo/) for validation [17].…”
Section: Data Collection and Processionmentioning
confidence: 99%
“…According to the recent published literature of m 6 A RNA methylation regulators in human cancer [15,16], 13 m 6 A RNA methylation regulators (METTL3, METTL14, WTAP, KIAA1429, RBM15, ZC3H13, YTHDC1, YTHDC2, YTHDF1, YTHDF2, HNRNPC, FTO, and ALKBH5) with available expression pro les in the TCGA-ESCA dataset were included ( Table 1). The Wilcoxon signed-rank test was applied to screen the differentially expressed m 6 A RNA methylation regulators between ESCA and normal tissues with P < 0.05.…”
Section: Identi Cation Of Differentially Expressed M 6 a Rna Methylatmentioning
confidence: 99%
“…Given the critical role of epigenetic regulation of DNA and histone (proteins) methylation in the underlying biological processes of mammals, the methyladenosine (mA) chemical modification of RNA may also be used as an novel epigenetic marker of far-reaching biological significance (1,2). N6-methyladenosine (m6A) is the most prevalent internal chemical modification of mRNAs in higher eukaryotes, at a frequency of approximately three sites per mRNA (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%